The Influence of Various Types of Local Microorganisms on Compost Quality Using the Berkeley Method on Kitchen Waste - Zairinayati; Rio Purnama (Gema Lingkungan Kesehatan, 2025)
The problem of organic waste is a big challenge for the environment, especially in urban areas. One effective solution is composting with the Berkeley method, with a rapid decomposition process within 18–21 days. This method uses high temperatures and regular turning of the compost. Berkeley composting not only helps reduce waste but also supports sustainable agriculture by providing a natural source of nutrients for the soil. This study aims to analyze the effect of three different types of MoL on compost quality, with parameters of temperature, pH, potassium, nitrogen, and phosphorus. Research method: This research is an experimental research through the utilization of dormitory kitchen waste with the Berkeley method and using MoL made from natural materials, namely fruit peels, bamboo shoots, and cassava tapai. Data analysis and processing using descriptive. The results showed that there was an effect of three types of MoL on the quality of compost. Based on observations of the physical quality of compost, the temperature and pH parameters showed that the average temperature was 29 0C and the average pH was 3.5, and the chemical examination of compost found that the compost produced for potassium parameters was highest produced by bamboo shoot mole, namely 0.044%, while the highest nitrogen parameter was tape mole, namely 1.41%, the highest phosphorus content was produced by fruit leather mole, namely 0.73 and the highest water content was fruit leather mole, namely 74.65. Conclusion: there is an effect of three types of MoL on the quality of compost with the Berkeley method.